THE ROLE OF INTERNATIONAL ORGANIZATIONS IN SUPPORTING PALESTINE'S RIGHT TO INDEPENDENCE - Shaban Al-Dalou; Ahmad Rifai (Universitas Duta Bangsa Surakarta, 2024)
International organizations have issued various resolutions and diplomatic efforts to support Palestinian independence. However, implementation on the ground continues to face significant obstacles due to the political interests of major powers and the lack of effectiveness in enforcing agreed resolutions. This study aims to examine the role of international organizations in supporting Palestine's right to independence.This research employs a literature study and qualitative analysis with a descriptive-analytical approach to understand the role of international organizations in supporting Palestinian independence. The study is based on academic sources, official documents, and credible news reports, ensuring data validity through source triangulation.The findings indicate that international organizations play a significant role in supporting Palestinian independence through diplomacy, humanitarian aid, human rights advocacy, and international law enforcement. However, various challenges, such as the political interests of major powers, vetoes in the UN Security Council, and the lack of concrete actions against Israel, remain major obstacles to achieving Palestinian independence. Therefore, more effective strategies and stronger coordination among international organizations are necessary to ensure that Palestinian independence is not merely a discourse but a reality in global politics.